A scoping study of urban community gardening promoted by the Philippine National Urban and Peri-urban Agriculture Banner Program (NUPAP) - Bayot, Ruvicyn S.; Schreinemachers, Pepijn; Mwambi, Mercy; Dominguez, Dulce D.; Oro, Emilita M.; Gonsalves, Julian F. (World Vegetable Center, 2023)
The promotion of urban and peri-urban agriculture (UPA) is recognized globally as an area with potential to improve food and nutrition security of urban residents. The government of the Philippines has recognized this and has implemented UPA and similar projects and programs since the 1970s. Support for these projects and programs has not been continuous. Interest in UPA was revived in 2022 with the National Urban and Peri-Urban Agriculture Banner Program (NUPAP), which was implemented by the Department of Agriculture (DA) with high-level support from the administration. The program rose in prominence during the COVID-19 when it became a cornerstone of the government’s response to maintain food and nutrition security. NUPAP is unique in the international context as it is a national program that receives support from all levels of government (national and sub-national) and engages multiple stakeholders (private sector, academics, research organizations, non-government organizations and people’s organizations). However, there is not a lot of documentation available that describes the program in a systematic and independent way, which is an important information gap that this study seeks to fill. Against this backdrop, this study aimed to gain a better understanding of the design and intended impacts of the NUPAP program. We chose to focus on NUPAP support for urban community gardens and commercial farms in the Metro Manila area. The study relied on a review of documents and interviews with government implementers, partners, and beneficiary communities.